Comparison of bedside ultrasonography and bedside chest radiography in neonatal peripherally inserted central catheters: A before and after self-control study - Liu, Xuexiu; Tao, Xiaojun; Xu, Ye; Zhang, Xianhong; Chen, Yanhan; Wu, Liping (Frontiers in Pediatrics, 2022)
Abstract Objective: To compare the applications of bedside ultrasonography (US) and bedside chest radiography (CR) in positioning peripherally inserted central venous catheter (PICC) at Neonatal Intensive Care Units (NICUs). Methods: The study is a prospective before and after self-control clinical trial. A consecutive series of 181 neonate patients were finally enrolled for PICC placement. CR, followed by US, was used to evaluate and readjust the sites of catheter tips. The imaging capability for PICC key structures, fluctuation of the measured data, measurement of tip-to-atrium distance, operation time, infants’ body temperature changes and direct expenses of the two imaging modalities were obtained and compared. Results: 1. Comparison in viewing PICC key structures: the display rate of catheter tip, SVC-and-right-atrium junction, IVC-and-right-atrium junction and tip-to-atrium distance is 99.47%, 100%, 100% and 99.47% for US and 100%, 98.42%, 97.37% and 95.79% for CR, respectively. 2. Fluctuation of the measured data by US and CR: the tip-to-atrium distance measured by US is 0.631 (0.435-0.820) cm; and that measured by CR is 0.593 (0.210-0.825) cm. US showed narrower range of datum variance. 3. Consistency and correlation between US and CR: for consistency analysis, Kappa coefficient (κ) was 0.843 (P < 0.05), showing their favorable consistency; for correlation analysis, Pearson correlation coefficient (r) was 0.739 (P < 0.05), suggesting a close correlation. 4. Comparison of operation time and infants’ body temperature drop: for a CR exam, the time period taken was significantly longer than that of US（59.7±26.33 vs79.6±28.06, P < 0.001); and CR operations caused a significant babies’ body temperature drop compared to US (0.14 ± 0.11 vs 0.34 ± 0.19, P < 0.001). 5. Comparison of the direct expenses: the total cost for CR positioning was significantly higher than that for US (¥153.99 yuan vs. ¥143 yuan, P = 0.026). Conclusion: US positioning of PICC tip exhibited superior traits to CR. We suggest that US can be used routinely for the neonates’ PICC placement at NICU.